First deep search of tidal tails in the Milky Way globular cluster NGC 6362 - Piatti, Andres Eduardo (2024)
I present results of the analysis of a set of images obtained in the field of the Milky Way globular cluster NGC 6362 using the Dark Energy Camera, which is mounted in the 4.0m Victor Blanco telescope of the Cerro-Tololo Interamerican observatory. The cluster was selected as a science case for deep high-quality photometry because of the controversial observational findings and theoretical predictions on the existence of cluster tidal tails. The collected data allowed us to build an unprecedented deep cluster field color- magnitude diagram, from which I filtered stars to produce a stellar density map, to trace the stellar density variation as a function of the position angle for different concentric annulii centered on the cluster, and to construct a cluster stellar density radial profile. I also built a stellar density map from a synthetic color-magnitude diagram generated from a model of the stellar population distribution in the Milky Way. All the analysis approached converge toward a relatively smooth stellar density between 1 and ∼ 3.8 cluster Jacobi radii, with a slightly difference smaller than 2 times the background stellar density fluctuation between the mean stellar density of the south-eastern and that of north-western hemispheres, the latter being higher. Moreover, the spatial distribution of the recently claimed tidal tail stars agrees well not only with the observed composite star field distribution, but also with the region least affected by interstellar absorption. Nevertheless, I detected a low stellar density excess around the cluster Jacobi radius, from which I conclude that NGC 6362 present a thin extra tidal halo.